The Effectiveness Of The Use Of Interactive Learning Media On Students' Mathematics Learning Outcomes - Sastika Astridewi; Sundanah sundanah; Eva Fitri Ningsih (Indonesian of Interdisciplinary Journal, 2025)
This study aims to determine the effectiveness of the use of interactive learning media on students’ mathematics learning outcomes. The background of this research is the low interest and learning outcomes of mathematics among students, which is thought to be due to conventional learning methods that do not involve active student participation so that student learning outcomes are low. Mathematics learning requires strategies and media that can increase student active engagement and help them understand concepts meaningfully. One alternative to address this issue is the use of interactive learning media that integrates visual and audio elements, as well as direct interaction with students. The research method used is quasi-experimental with a pretest-posttest control group design. The population in this study was 11th grade students of SMAN 8 Pandeglang and the experimental class using lecture learning media. The instruments used were descriptive questions and student questionnaires. The results of data analysis using the t-test show that there is a significant difference between the learning outcomes of students who use interactive learning media and those who use conventional learning media. This shows that interactive learning media is more effective in improving students’ mathematics learning outcomes.